Pengetahuan Ibu Tentang Kebutuhan Gizi Seimbang Dengan Pertumbuhan Anak Dalam Upaya Meningkatkan Gizi Anak - Endang Khoirunnisa; Wiwin Hindriyawati; Diyah Paramita Nugraha (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2015)
Background: Children is a loving couple, the parents should be responsible for the health and welfare of theirchildren. Child welfare is alive bearing the security, tranquility, and prosperity for children both spiritually and temporally. Prosperous state will be achieved when a child needs both spiritual and physical can be fulfilled, then theneed for it in an effort to achieve these goals, which can be a way of increasing the economic income families or theelderly. The growth and development of children is the result of an interaction between genetic factors-hereditaryconstitutional and environmental factors, both prenatal and environmental surroundings postnatal the growth ofchildren affected by dietary factors (nutrition) and genetic.Objective: To improve the nutrition of children in order to obtain optimal growth in the region of 2 health centersSewon Bantul.Objective: In a study that will be conducted by researchers, the objectives to be achieved are: to improve childnutrition in order to obtain optimal growth in the area of health centers Sewon 2 Bantul.Methods: This study was a quantitative study using a study design was cross-sectional. This type of research iscross sectional. In this type, the independent and dependent variables assessed simultaneously at any one time,so there was no follow-upResults:The higher the mother’s knowledge, the better growth in children. Knowledge contributes to the growth ofchildren as an effort to improve child nutrition. an increase in the mother’s knowledge will be in line with the growthof children. The knowledge of the mother is associated with the growth of children, which depicts a mother in caringfor her child in the subject of children’s growth as undertakings improving child nutritionConclusion: There is a relationship between maternal knowledge about nutritional needs balanced with the growthof the child in an effort to improve gisi child health centers in the region of 2 Sewon BantulKeywords: Knowledge, balanced nutrition